Different proactive and reactive action control in fencers` and boxers` brain - Bianco, V.; Di Russo, F.; Perri, R. L.; Berchicci, M. (Neuroscience, 2017)
Practicing sport at top level requires excellent physical and cognitive skills. The goal of the present study was to investigate whether specific sport practice may affect the preparation-perception-action stages of processing during a visuo-motor task requiring perceptual discrimination and fast response. We recruited 39 participants (two groups of professional fencers and boxers, and a control group; N = 13 for each group) and measured behavioral performance and event-related potentials (ERPs) while performing a go/no-go task. Results revealed that athletes were faster than controls, while fencers were more accurate than boxers. ERP analysis revealed that motor preparation, indexed by the Bereitschaftspotential (BP), was increased in athletes than controls, whereas the top-down attentional control, reflected by the prefrontal negativity (pN) component, was enhanced only in fencers when compared to controls. Most of the post-stimulus ERPs i.e. the N1, the N2, the P3, and the pP2, were enhanced in fencers. Combat sports require fast action execution, but the preparatory brain activity might differ according to the specific practice required by each discipline. Boxers might afford to commit more errors (as reflected by high commission error (CE) rate and by a small pN amplitude), while fencers have to be as much fast and accurate as possible (thanks to an enhanced pN amplitude). Although the possible influence of repetitive head blows on cerebral activity cannot be excluded in boxers, our results suggest that cognitive benefits of high-level sport practice might also be transferred to the daily (i.e., no sport-related) activities.